Dislocation loop formation by swift heavy ion irradiation of metals. (12th June 2017) - Khara, Galvin S; Murphy, Samuel T; Duffy, Dorothy M
Abstract: A coupled two-temperature, molecular dynamics methodology is used to simulate the structural evolution of bcc metals (Fe and W) and fcc metals (Cu and Ni) following irradiation by swift heavy ions. Electronic temperature dependent electronic specific heat capacities and electron–phonon coupling strengths are used to capture the full effects of the variation in the electronic density of states. Tungsten is found to be significantly more resistant to damage than iron, due both to the higher melting temperature and the higher thermal conductivity. Very interesting defect structures, quite different from defects formed in cascades, are found to be created by swift heavy ion irradiation in the bcc metals. Isolated vacancies form a halo around elongated interstitial dislocation loops that are oriented along the ion path. Such configurations are formed by rapid recrystallization of the molten cylindrical region that is created by the energetic ion. Vacancies are created at the recrystallization front, resulting in excess atoms at the core which form interstitial dislocation loops on completion of crystallization. These unique defect structures could, potentially, be used to create metal films with superior mechanical properties and interesting nanostructures.